The effect of supercritical CO2 on shaly caprocks - Hadian, Pooya; Rezaee, Reza (MDPI, 2019)
The effect of supercritical CO2 on the shaly caprocks is one of the critical issues to be considered in CO2 sequestration programs. Shale-scCO2 interactions can alter the seal integrity, leading to environmental problems and bringing into question the effectiveness of the program altogether. Several analytical studies were conducted on samples from Jurassic Eneabba Basal Shale and claystone rich facies of the Triassic Yalgorup Member (725–1417 m) in the Harvey CO2 sequestration site, Western Australia, to address the shale-scCO2 interactions and their effect on the petrophysical properties of the caprock. Shale samples saturated with NaCl brine were exposed to scCO2 under the reservoir condition (T = 60 ◦C, P = 2000 psi) for nine months and then tested to determine their altered mineralogical, petrophysical and geochemical properties. The experimental study examined changes to the mineralogical composition, capillary threshold pressure, and pore size distribution (PSD) of samples. The X-ray diffraction (XRD) results showed several changes in mineralogy because of rock-brine-CO2 reactions. Quartz, feldspars, kaolinite, and goethite were dissolved in most samples and muscovite, and halite were precipitated in general. Nuclear magnetic resonance (NMR), low-pressure nitrogen adsorption (LPNA), and mercury injection capillary pressure (MICP) tests indicate an increase in pore volume, except for relatively tighter, clay-rich samples. A reduction in capillary threshold pressures of samples after exposure to scCO2 is observed.